Copy Number Variation Screen Identifies a Rare De Novo Deletion at Chromosome 15q13.1-13.3 in a Child with Language Impairment. - Kerry A Pettigrew; Emily Reeves; Ruth Leavett; Marianna E Hayiou-Thomas; Anahita Sharma; Nuala H Simpson; Angela Martinelli; Paul Thompson; Charles Hulme; Margaret J Snowling; Dianne F Newbury; Silvia Paracchini (PLoS ONE)
A significant proportion of children (up to 7% in the UK) present with pronounced language difficulties that cannot be explained by obvious causes like other neurological and medical conditions. A substantial genetic component is predicted to underlie such language problems. Copy number variants (CNVs) have been implicated in neurodevelopmental and psychiatric conditions, such as autism and schizophrenia, but it is not fully established to what extent they might contribute to language disorders. We conducted a CNV screen in a longitudinal cohort of young children with language-related difficulties (n = 85), focusing on single events at candidate loci. We detected a de novo deletion on chromosome 15q13.1-13.3. The adjacent 15q11-13.1 locus is disrupted in Prader-Willi and Angelman syndromes, while disruptions across the breakpoints (BP1-BP6) have previously been implicated in different neurodevelopmental phenotypes including autism, intellectual disability (ID), seizures and developmental delay (DD). This is the first report of a deletion at BP3-BP5 being linked to a deficit confined to language impairment, in the absence of ID, expanding the range of phenotypes that implicate the chromosome 15q13 locus.